Does the MMPI-2 College Maladjustment Scales Affect the Mini-Quiz Score of Students in the Medical Study Program of Universitas Muhammadiyah Yogyakarta - Sri Sundari; Fitri Nurjanah (Universitas Muhammadiyah Yogyakarta, 2021)
A student, especially a new student, will make adjustments to their environment in their first year of college, from high school to higher education. During the adjustment process, freshman experience various kinds of changes in the Higher Education environment. These changes both academically and non-academically. This research is a quantitative analytic observational research with cross sectional approach. The population used in this study were new students of the 2018 class of the Medical Study Program at Universitas Muhammadiyah Yogyakarta. There were 150 new student batch 2018 as population of the study. Based on the results and discussion, it can be concluded that there is no significant relationship between the MMPI-2 College Maladjustment Scales (Mt) and the mini-quiz score. It is suggested to have further research with more mini-quiz scores in blocks, research on factors that affect learning outcomes, and involve other aspects of learning outcomes, not only mini-quiz scores but also final block evaluation scores, tutorial scores and practicum scores.